Optimal disturbance rejection controllers design for synchronised output regulation of time‐delayed multi‐agent systems. Issue 7 (8th February 2017) - Ye, Fei; Zhang, Weidong; Ou, Linlin; Zhang, Guoqing
Abstract : An optimal disturbance rejection controller design method is put forward analytically for the synchronised output regulation of time‐delayed multi‐agent systems (MAS). All kinds of linear MAS can be described by a novel block diagram based on transfer functions in a unified framework. For each subsystem without intercommunication, the optimal output, input and balancing output–input load disturbance rejection controllers are designed independently. A filter is used to be in series with each controller to not only stabilise the whole systems but also achieve a tradeoff between nominal performance and robustness by adjusting a single tuning parameter. The proposed distributed H 2 controllers calculated by algebraic solution perform better capacity of disturbance attenuation than the conventional given‐structured protocols. Two simulation examples demonstrate the validity of the new algorithm.